Melatih Literasi Matematis Siswa dengan Metode Naive Geometry - Maria Ulfa; Ahmad Lubab; Yuni Arrifadah (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2017)
The aim of this research is to measure mathematical literacy skills of a student after mathematics learning processes using naive geometry method on the quadratic equation. This research is using quantitative methods. This research was implemented at SMP Ulul Albab. The mathematical literacy skills obtained from observation and mathematics literacy tests which refer to the mathematics literacy indicator. The tests were given after a teaching and learning process using naive geometry while observation was done during the learning process. The results show that 22.73% students have high mathematical literacy skill, 68.18% students have intermediate mathematical literacy, and 9.09% students who have low math skills literacy.